Development of a Custom Extracorporeal Circuit for Endovascular Resuscitation Research - Abdou, Hossam; Richmond, Michael; Madurska, Marta J; Elansary, Noha; Morrison, Jonathan J (Journal of Endovascular Resuscitation and Trauma Management, 2020)
Our aim was to demonstrate the utility and applicability of in vitro extracorporeal circuits in endovascular resuscitation research. The method for building an inexpensive in vitro extracorporeal circuit for endovascular resuscitation research is described. In this study, aortic cannulas and pump combinations were evaluated in the in vitro extracorporeal circuit. Then one aortic cannula and pump set up was evaluated in a post-mortem swine model. Flow data was collected and compared among groups. The peristaltic pump generated the highest flow as compared with the other pump combinations at any given catheter size. The peristaltic pump combined with the 10 Fr cannula produced the highest flow overall at 2,304 ml/min. This same combination produced a peak flow of 886 ml/min at the aortic root in the swine model. The flow generated in the swine model was less than half of that generated in the in vitro model. However, all flow was channeled through one outflow tract in the in vitro model whereas the swine aorta has several branches of outflow. As such, a 50% reduction in flow or greater is anticipated at the level of the aortic root. An in vitro extracorporeal circuit for endovascular research can be built for less than US10,000, with most of the materials being reusable, and can be used to generate representative data that may be anticipated in a swine model.